2016
DOI: 10.1055/s-0035-1561970
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Synthesis of NODASA-Functionalized Peptide

Abstract: All the chemicals were purchased from commercial sources and used without further purification. Mono-methyl fumarate, tert-butyl bromoacetate, N,N-diisopropylethylamine (DIPEA), lithium hydroxide (LiOH), tetrahydrofuran (THF), dichloromethane (DCM), dimethylformamide (DMF) were purchased form Sigma-Aldrich. 1,4,7 triazacyclononane was purchased from Leap LabChem. Fmoc-Phe-OH, Fmoc-Gly-OH, Fmoc-Tyr (tBu)-OH,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…This prompted us to investigate the cyclic zinc chelator’s capacity to inhibit MBLs when attached to a BL moiety, which should improve the molecule’s overall pharmacological properties. BP1 was synthesized in five steps through a procedure adapted from Dutta et al…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This prompted us to investigate the cyclic zinc chelator’s capacity to inhibit MBLs when attached to a BL moiety, which should improve the molecule’s overall pharmacological properties. BP1 was synthesized in five steps through a procedure adapted from Dutta et al…”
Section: Resultsmentioning
confidence: 99%
“…This prompted us to investigate the cyclic zinc chelator's capacity to inhibit MBLs when attached to a BL moiety, which should improve the molecule's overall pharmacological properties. BP1 37 was synthesized in five steps through a procedure adapted from Dutta et al 38 A desirable β-lactamase inhibitor should simultaneously neutralize MBLs, while preserving the activity of existing carbapenem antibiotics, thereby targeting antimicrobial resistance and restoring the efficacy of BLs. BP1 demonstrated the potential to achieve this, as observed in the in vitro experiments.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…† An alternative route was envisaged whereby we first attach the β-lactam to the chelator, followed by the alkylation in order to provide enough steric hindrance to prevent the over-alkylation step. We synthesised 11 using a procedure reported by Dutta et al , 38 1,4,7-triazanonane (10) underwent a Michael-addition reaction with mono-methyl fumarate to afford 11 in excellent yields (>95%) ( Scheme 2 ). Compound 11 was Boc-protected to afford 12 in yields of 85–96% after purification on a silica gel column.…”
Section: Resultsmentioning
confidence: 99%
“…NODASA, 2-(4,7-bis(carboxymethyl)-1,4,7-triazonan-1-yl) succinic acid, is a NOTA derivative that was synthesized for radiolabeling with gallium. The stability constant of 68 Ga-NODASA ( Table 4 ) is not much different from the value of the stability constant of 68 Ga-NOTA ( Table 4 ) [ 109 , 142 , 143 ]. The in vivo stability of 68 Ga-NODASA in blood serum showed that there was no transchelation with transferrin in blood serum for five days of observation; it can be said that 68 Ga-NODASA had high in vivo stability.…”
Section: Bifunctional Chelator Used In Radiopharmaceutical Agentsmentioning
confidence: 87%
“…The results showed that the 68 Ga-NODASA complex remained 100% for five days of observation. The high stability of the 68 Ga-NODASA complex promises to produce stable radiopharmaceutical agents [ 109 , 134 , 142 , 143 ].…”
Section: Bifunctional Chelator Used In Radiopharmaceutical Agentsmentioning
confidence: 99%